2014
DOI: 10.1007/s00380-014-0507-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of periodontitis in Japanese patients with cardiovascular diseases: a comparison between abdominal aortic aneurysm and arrhythmia

Abstract: Although there is a link between periodontitis and cardiovascular disease (CVD), the influence of periodontitis on CVD is unclear. The aim of this study was to assess the relationship between periodontal bacterial burden and CVD. We studied 142 patients with tachyarrhythmia (TA) and 25 patients with abdominal aortic aneurysm (AAA). We examined periodontitis and the presence of Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans and Prevotella intermedia in the patients' saliva and subgingival plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…8) Another paper revealed that patients with AAA had fewer remaining teeth and deeper periodontal pocket depth compared to patients with arrhythmia. 7) Thus, periodontitis may affect the development of an aortic aneurysm in both Marfan and non-Marfan patients. The reason the aorta was affected in different locations remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8) Another paper revealed that patients with AAA had fewer remaining teeth and deeper periodontal pocket depth compared to patients with arrhythmia. 7) Thus, periodontitis may affect the development of an aortic aneurysm in both Marfan and non-Marfan patients. The reason the aorta was affected in different locations remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…6) We also showed that periodontitis was frequently observed in patients with an abdominal aortic aneurysm (AAA). 7,8) However, the causal relationships among MFS, aortic aneurysms, and periodontitis still have to be elucidated. Thus, the aim of this study was to clarify the pathophysiological association between SoV dilatation and periodontitis in patients with MFS.…”
mentioning
confidence: 99%
“…In his study conducted in Japan during 2013, Suzuki et al 3 reported the study of 142 patients with arrhythmias and 25 aneurysms of the abdominal aortic artery, determining the presence of Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia in samples of dental plaque analyzed by PCR and levels of antibodies against these bacteria were measured simultaneously, obtaining higher serological titles in patients who developed aneurysms compared to those who suffered arrhythmias. 3 During the same period, Hanaoka et al 4 determined the serum levels of response against Porphyromonas gingivalis and he related them to the presence of hypertension and atherosclerosis in a group of 127 patients, mostly male, where high levels of antibodies were found. In turn, the serological title was correlated with the progress of both periodontal disease and hypertension and atherosclerosis.…”
Section: Oral Microbiota Realted With Various Cardiovascular Diseasesmentioning
confidence: 99%
“…Suzuki et al [20] compared 12 patients with abdominal AA with 24 age-and sex-matched CVD patients without abdominal AA and found that AA patients had deeper periodontal pockets than controls, despite the fact that there was no difference in the number of remaining teeth or in the populations of periodontal bacteria in oral samples. The same authors compared the prevalence of periodontitis among 25 abdominal AA patients and 142 arrhythmia patients and found that the AA patients had significantly fewer remaining teeth and deeper pockets compared with patients with arrhythmia, despite the fact that the periodontal bacteria present in saliva or subgingival plaque and serum antibodies were comparable between the AA and arrhythmia groups [21]. A study by Ding et al [22] comparing 89 AA patients with 59 ageand sex-matched controls found that the prevalence of periodontal pathogens was higher in the oral samples of AA patients than in the samples of controls; importantly, some oral pathogens were detected in dissected aneurysm samples.…”
Section: Association Between Dental Disease and Cardiovascular Diseasementioning
confidence: 99%